Bioponic system for nitrogen and phosphorus recovery from chicken manure: Evaluation of manure loading and microbial communities. (15th April 2021) - Wongkiew, Sumeth; Koottatep, Thammarat; Polprasert, Chongrak; Prombutara, Pinidphon; Jinsart, Wanida; Khanal, Samir Kumar
Graphical abstract: Highlights: Chicken manure-based bioponics was effective in N and P release for plant growth. Chicken manure loadings of 200–400 g dry wt./18 plants provided enough nutrients. Bioponics achieved N and P use efficiencies up to 41.8% and 8.0%, respectively. Microbial communities worked symbiotically in generating available N and P. Organic decomposers were key groups in maintaining superior bioponic performance. Abstract: Bioponics integrates the biological treatment of nutrient-rich waste streams with hydroponics. However, there are several challenges of bioponics, especially nutrient availability and qualities, which affect plant yield. In this study, chicken manure based-nutrient film technique bioponics was examined at manure loadings of 200, 300, and 400 g dry wt. per bioponic system (total of 18 plants). Bioponics effectively released nitrogen and phosphorus (total ammonia nitrogen of 5.8–8.0 mgN/L, nitrate of 7.0–11.2 mgN/L, and phosphate of 48.7–74.2 mgP/L) for efficient growth of lettuce ( Lactuca sativa ; total yield of 1208–2030 g wet wt. per 18 plants). Nitrogen and phosphorus use efficiencies were 35.1–41.8% and 6.8–8.0%, respectively, and were comparable to aquaponics. Next-generation sequencing was used to examine the microbial communities in digested chicken manure and plant roots in bioponics. Results showed that several microbial genera were associated with organic degradation (e.g., Nocardiopsis spp., Cellvibrio spp.), nitrification ( Nitrospira spp.), phosphorus solubilization, and plant growth promotion (e.g., WD2101_soil_group, and Bacillus spp.). Nocardiopsis spp., Romboutsia spp . and Saccharomonospora spp. were found at high abundances and a high degree of co-occurrences among the microbiota, suggesting that the microbial organic decomposition to nitrogen and phosphorus release could be the key factors to achieve better nutrient recovery in bioponics.